A correlation of trans cerebellar diameter by ultrasonography and gestational age in second and third trimester (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Increased perinatal mortality incidence has been seen amongst patients whose precise gestational age is unknown. Trans cerebellar diameter is a newer parameter in the estimation of gestational age. Therefore, the present study was conducted with the aim to determine the accuracy of trans cerebellar diameter in predicting gestational age during second and third trimester of pregnancy.Materials and Methods: The present study was conducted in the Mithila Hospital,Janakpurdham for a period of 1 year. The study included a total of 160 females with singleton pregnancies during their 2nd or 3rd trimester. The characteristic butterfly appearance of the cerebellum hinted the location of posterior fossa. All the data was arranged in a tabulated form and analyzed statistically. Data was expressed in the form of mean with standard deviation. SPSS software16 was used for the analysis of the data.Results: The present study enrolled 160 subjects, out of which 80 were in their second trimester and 80 were in their third trimester.  The mean transcerebellar diameter of subjects in second trimester was 20.22±4.87 and it was 36.01±2.89 amongst subjects in their third trimester. As the gestational age advances, the transcerebellar diameter also increases with it in a linear manner.Conclusion: Transcerebellar diameter can be used as a reliable parameter to estimate the gestational age and is also not altered in cases of intrautering growth restriction.